Inflammatory inert poly(ethylene glycol)–protein wound dressing improves healing responses in partial‐ and full‐thickness wounds - Shingel, Kirill I (Int Wound J, 2006)
In this study, a novel soft hydrogel system based on the poly(ethylene glycol)–protein conjugates was evaluated as an occlusive wound dressing material. The hydrogel material, referred by the name of BioAquacare™, contains up to 96% of the liquid and is formulated with phosphate‐buffered saline and safe preservative to control bacterial load in the open wounds. Performance of the BioAquacare™ as a wound dressing material was assessed in partial‐ and full‐thickness wounds in pigs. Wound analysis comprised macroscopic determination of the wound size, histological examination of the healing tissues and biochemical characterisation of wound exudates. The wounds treated with BioAquacare™ healed without any signs of inflammation, skin irritation, oedema or erythema. Cellular composition of the reepithelialised wounds was very similar to that of the normal skin, with a well‐developed stratum corneum and epithelial layer. It was observed that BioAquacare™ plays the role of a liquid compartment, which provides pronounced hydration effect and helps maintain a natural moist environment of the healing tissues. BioAquacare™ showed relatively low protein‐absorbing activity, absorbing predominantly low‐molecular‐weight molecules, including interleukin (IL)‐1β, IL‐6, transforming growth factor‐β1 and products of haemoglobin degradation. It is concluded that application of the moist BioAquacare™ dressing promotes fast reepithelialisation by creating favourable environment for keratinocytes proliferation and it also reduces scarring. The results show that BioAquacare™ can be considered as a safe, biocompatible and inflammatory inert wound dressing material.